Prospects of Dual Form of Teaching and Learning in the Realities of the Covid-19 Pandemic and the Post-pandemic Period - Bratitsel, Maryna; Братицель, Марина; Kravchuk, Olena; Кравчук, Олена; Tishko, Liliya; Тішко, Лілія Володимирівна; Osiievskyi, Valerii; Осієвський, Валерій; Bellie, Victoriia; Беллі, Вікторія (International Journal of Computer Science and Network Security (South Korea),IJCSNS, 2021)
The COVID-19 pandemic has posed significant community challenges towards higher education around the world. The urgent and unexpected request for full-time university courses to switch over to online teaching was a particular challenge. Online learning and learning imply a certain pedagogical knowledge content (PKC), mainly related to the design and organization for better learning and the creation of unique learning environments using digital technologies. With the help of the present academic paper, we provide some expert opinion on the PKC connected with online learning with the aim of helping non-university professionals (that is, those with lack of online learning experience) navigate these challenging times. Our findings point to the planning of learning activities with certain features, a combination of three types of presence (social, cognitive and facilitative) and the need to adapt the assessment system to new learning requirements. We will conclude by contemplating on how responding to a crisis can improve teaching and learning practices in the post-digital era Пандемія COVID-19 поставила перед громадою значні проблеми вищої освіти в усьому світі. Особливим викликом був терміновий і неочікуваний запит щодо переходу на курси денної форми навчання в університетах на онлайн-викладання. Онлайн-навчання та навчання мають на увазі певний зміст педагогічних знань (PKC), переважно пов’язаний з проектуванням та організацією для кращого навчання та створення унікальних навчальних середовищ з використанням цифрових технологій. За допомогою цієї наукової роботи ми надаємо деяку експертну думку щодо PKC, пов’язаного з онлайн-навчанням, з метою допомогти неуніверситетським фахівцям (тобто тим, хто не має досвіду онлайн-навчання) орієнтуватися в ці складні часи. Наші висновки вказують на планування навчальної діяльності з певними особливостями, поєднанням трьох типів присутності (соціальної, когнітивної та фасилітативної) та необхідністю адаптації системи оцінювання до нових вимог навчання. На завершення ми поміркуємо над тим, як реагування на кризу може покращити викладання та навчання в постцифрову еру.
Перспективи подвійної форми викладання і навчання в реаліях пандемії Covid-19 та постпандемічного періоду
Keywords: online learning; онлайн-навчання; emergency; надзвичайна ситуація; COVID-19; COVID-19; higher education; вища освіта; pedagogical knowledge content (PKC); зміст педагогічних знань (PKC); instructional design; навчальний дизайн